The Counterbalance of Skin Metabolism on Orbits and Diseases - Li-Fan Chuang; Chin-Kong Hsu; Hong-Nong Chou; Hung-Shih Chou; Ping-Jyun Sung; Chia-Ching Chen; Fu-Gin Chen (Medical Sciences, 2015)
Human organ functions are regulated by the nervous system. When human cells receive a message, this message is transmitted to the nervous system through a series of signal transmission processes. Skin conditions that occur after applying skin cream are closely related to signal transmission and nervous regulation. We determined the connection between signal regulation and natural rhythmic operations. The diurnal variations resulting from the earth’s rotation and indicate the relative relationships between the sympathetic nervous system and the parasympathetic nerve system. A spectrum was developed to assess neural transmission conditions by using skin signals which from Fourier transformation of the waves and established the association between the spectrum and diseases. The results could explain the relationships between the neurological illnesses and established spectrum. The objective was to promote the use of this spectrum as a new tool for conducting the nervous system tests in the future.